Effects of dietary tea polyphenols on growth, biochemical and antioxidant responses, fatty acid composition and expression of lipid metabolism related genes of large yellow croaker (Larimichthys crocea). (26th December 2017) - Ji, Renlei; Li, Yicong; Li, Xueshan; Xiang, Xiaojun; Li, Yongnan; Zhu, Si; Yang, Bo; Zhang, Yanjiao; Mai, Kangsen; Ai, Qinghui
Abstract: The study was conducted to investigate the effects of dietary tea polyphenols (TP) on growth performance, biochemical and antioxidants responses, fatty acid composition, and lipid metabolism‐related gene expressions of large yellow croaker (Larimichthys crocea ). Four diets were formulated with different levels of TP (0.00%, 0.01%, 0.02% and 0.05%). Results showed that growth performance of L. crocea were not different among dietary treatments. Compared with the control group, fish in 0.02% TP group had lower body and hepatic lipid content and lower total cholesterol content. The minimum content of triglycerides and low‐density lipoprotein‐cholesterol were found in 0.05% TP group. Hepatic n‐6 PUFA and n‐3 PUFA were significantly higher in TP supplementation groups. Malondialdehyde content was lower in TP supplementation groups, and superoxide dismutase activity was higher in 0.01% TP group than the control group. The mRNA expressions of carnitine palmitoyltransferase1, acyl‐CoA oxidase and peroxisome proliferators‐activated receptor α were up‐regulated in 0.01% and 0.02% TP groups, while lipoprotein lipase expression was down‐regulated in TP supplementation groups than the control group. Results suggested that 0.01%–0.02% TP supplementation could reduce the deposition of liver lipid of L. crocea caused by high‐lipid diet, which might be due to the increase in lipid oxidation related gene expressions.